THE CLEAVING ACTIVITY ASSAY ON SUPERCOILED DNA BY PROTEIN FRACTIONS FROM Morinda citrifolia LEAVES - Nanik Sulistyani; Sismindari .; Sudjadi . (Indonesian Journal of Pharmacy, 2002)
Study on supercoiled DNA cleaving activity assay of protein fraction from Morinda citrifolia leaf had been done. The aim of this research is to compare the supercoiled DNA cleaving abilities among the fractions. This is a preliminary screening to find RIP from Morinda citrifolia Fractionation of protein was done by adding Ammonium Sulphate up to 20%, 40%, 60%, 80% and 100% in the crude extract, saturated solution was then centifugated to get the pellet fractions and coded as F-20, F-40, F-60, F-80 and F-100. The mixture of pUC19 plasmid and protein fractions, in the same protein concentration were incubated at room temperature for one hour, the cleaving ability of protein fraction on supercoiled DNA.was investigated. The results indicated that protein fractions, of F-80 had the highest cleaving activity to supercoiled DNA.Key words : Ribosome-Inactivating Protein (RIP), supercoiled DNA , protein fraction, Morinda citrifolia.